(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objectives of this study were to study the factors of marketing mix which affect to purchasing decision of street food in Samutprakarn and study about purchasing decisions of street food in Samutprakarn. The survey research is applied to this study. The sample of this research is the people that consume street food in Samutprakarn in January to February 2018 for the number of 323 people and used questionnaires as the tool for collecting the information.The results of this study found out the target group who have different age, different status and different career affected to the purchasing decision of street food in Samutprakarn differently. The factors of marketing mix which affected to purchasing decision of street food in Samutprakarn include product, place and promotion by focusing on benefiting for heath, the taste of food, placed in shopping area and online advertising affected to purchasing decisions of street food in Samutprakarn by having statistical significance at 0.05